1999
DOI: 10.1002/hep.510300421
|View full text |Cite
|
Sign up to set email alerts
|

Expression of inositol 1,4,5-trisphosphate receptor isoforms in rat cirrhosis

Abstract: Ca 2؉ signals mediate the hepatic effects of numerous hormones and growth factors. Hepatic Ca 2؉ signals are elicited by the inositol trisphosphate receptor, an intracellular Ca 2؉ channel. Three isoforms of this receptor have been identified; they are expressed and regulated differently. We investigated the effect of liver fibrosis and cirrhosis on the hepatic expression of the inositol trisphosphate receptor isoforms. Two different rat models were used: bile duct ligation (fibrosis) and chronic exposure to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…Real Time Polymerase Chain Reaction-Real time PCR analysis was performed using an Applied Biosystems 7700 sequence detector (Foster City, CA) as described (22). Sets of primers were chosen for each InsP 3 R isoform and for glyceraldehyde-3-phosphate dehydrogenase to give PCR products less than 100 base pairs in length.…”
Section: Cytosolic Camentioning
confidence: 99%
“…Real Time Polymerase Chain Reaction-Real time PCR analysis was performed using an Applied Biosystems 7700 sequence detector (Foster City, CA) as described (22). Sets of primers were chosen for each InsP 3 R isoform and for glyceraldehyde-3-phosphate dehydrogenase to give PCR products less than 100 base pairs in length.…”
Section: Cytosolic Camentioning
confidence: 99%
“…1a). SkHep1 cells were found to express the type II InsP3R, which is the most prevalent isoform in liver (16,29). The subcellular distribution of the InsP 3 receptor was investigated by confocal immunofluorescence.…”
Section: Characterization Of Camentioning
confidence: 99%
“…Subcellular fractionation experiments with these cells have shown that the receptor does not always co-purify with ER markers but rather with markers of the plasma membrane (Lièvremont et al, 1994;Sharp et al, 1992). Immunocytochemical experiments have indicated that the InsP3R is mainly concentrated at the lateral pole of polarized MDCK cells (Bush et al, 1994;Zhang et al, 2003) and near the apical pole of other polarized cells such as hepatocytes, (Dufour et al, 1999;Nathanson et al, 1994a), cholangiocytes (Hirata et al, 2002), pancreatic acinar cells and parotid cells (Lee et al, 1997;Nathanson et al, 1994b;Yule et al, 1997). In pancreatic acinar cells, the three receptor sub-types displayed the same sub-apical localization, indicating that this pattern of localization does not depend on the receptor subtype.…”
mentioning
confidence: 99%